2021
DOI: 10.1200/jco.2021.39.15_suppl.tps5595
|View full text |Cite
|
Sign up to set email alerts
|

AdvanTIG-202: A phase 2 study investigating anti-TIGIT monoclonal antibody ociperlimab plus anti-PD-1 monoclonal antibody tislelizumab in patients with previously treated recurrent or metastatic cervical cancer.

Abstract: TPS5595 Background: Women with recurrent/metastatic cervical cancer represent a poor prognostic group with high unmet clinical needs. T-cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibition motif domains (TIGIT) is a co-inhibitory, immune checkpoint receptor expressed on immune cells and upregulated on T-cells and natural killer cells in multiple solid tumors, inhibiting anticancer immune responses. Ociperlimab (BGB-A1217) is a novel, humanized, monoclonal antibody that binds TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This drug binds to the extracellular domain of human TIGIT with high affinity and blocks the interaction between TIGIT and its ligand CD155 or CD112 while preserving intact Fc segment function, which is essential for its antitumor activity; it exerted synergistic antitumor effects when combined with anti-PD-1/PD-L1 mAbs [ 176 ]. The results of Phase I clinical trials designed to evaluate ociperlimab combined with tislelizumab (anti-PD-1 mAb) were first reported at ASCO in 2021, and they confirmed that ociperlimab combined with tislelizumab was well tolerated; moreover, antitumor efficacy was observed in patients with advanced solid tumors (NCT04693234) [ 177 ]. In June 2023, a Phase III clinical trial evaluating the efficacy and safety of ociperlimab in combination with tislelizumab and platinum-based doublet chemotherapy as first-line treatment for patients with locally advanced or metastatic NSCLC without an operational driver mutation was initiated (NCT05791097).…”
Section: Clinical Trials Of Anti-lag-3 Anti-tim-3 and Anti-tigit Mabsmentioning
confidence: 97%
“…This drug binds to the extracellular domain of human TIGIT with high affinity and blocks the interaction between TIGIT and its ligand CD155 or CD112 while preserving intact Fc segment function, which is essential for its antitumor activity; it exerted synergistic antitumor effects when combined with anti-PD-1/PD-L1 mAbs [ 176 ]. The results of Phase I clinical trials designed to evaluate ociperlimab combined with tislelizumab (anti-PD-1 mAb) were first reported at ASCO in 2021, and they confirmed that ociperlimab combined with tislelizumab was well tolerated; moreover, antitumor efficacy was observed in patients with advanced solid tumors (NCT04693234) [ 177 ]. In June 2023, a Phase III clinical trial evaluating the efficacy and safety of ociperlimab in combination with tislelizumab and platinum-based doublet chemotherapy as first-line treatment for patients with locally advanced or metastatic NSCLC without an operational driver mutation was initiated (NCT05791097).…”
Section: Clinical Trials Of Anti-lag-3 Anti-tim-3 and Anti-tigit Mabsmentioning
confidence: 97%
“…The findings were reported to be all-dose-tolerable in advanced solid tumors with promising antitumor activity [ 192 ]. On top of that, this combination treatment strategy was also conducted in several other clinical studies, including AdvanTIG-202 (phase II) [ 193 ], AdvanTIG-203 (NCT04732494, phase II) [ 194 ], AdvanTIG-206 (NCT04948697, phase II) [ 195 ], and AdvanTIG-302 (NCT04746924, phase III) [ 196 ].…”
Section: Clinical Trials Of Anti-tigit Agentsmentioning
confidence: 99%
“…In a phase I study, the combination of tislelizumab and ociperlimab resulted in an ORR of 4.2% (1/24) and a DCR of 41.7% (10/24) in previously treated patients, without causing grade ≥4 treatmentrelated adverse events (TRAEs). 39 Besides, several trials investigating the effect of this combination are ongoing, [66][67][68][69] the results of which are worth expecting.…”
Section: Efficacy Of Tislelizumab In Other Settingsmentioning
confidence: 99%